Research on Unmanned Driving Interface Based on Lidar Imaging Technology - Wang, Yuli; Zhu, Yanfei; Liu, Hui (Frontiers in Physics, 2022)
In a sense, unmanned intelligent vehicle is a kind of intelligent autonomous mobile robot, it mainly uses some of the sensors installed to collect the roads around their own environmental information, these information processing and control intelligent vehicle speed and steering, so that the intelligent vehicle can safely and reliably achieve the goal of unmanned in the road. This topic mainly use vehicle-mounted camera, laser scanning radar and other sensors to collect real-time environmental information, for good processing and analysis detected the specific location and shape of the obstacle.This study investigated the impact of two In-Vehicle Information Systems (IVISS) on both usability and driving safety. The environmental perception module is an important part of the driverless car．The function of the system is to transmit the surrounding environment of the driverless vehicle's current driving area to the vehicle system through the laser perception sensing technology. We simulated vehicle checkerboard and hierarchical IVIS interface layouts and examined their usability based on task completion time, error rate, NASA-TLX, and System Usability Scale (SUS). This study offers empirical evidence for IVIS interface design.